Rhetorical structure of introduction chapters written by novice Vietnamese TESOL postgraduates - Loan Thi Thuy Nguyen,; Issra Pramoolsook, (Pusat Pengajian Bahasa dan Linguistik, FSSK, UKM, 2014)
It is generally agreed that writing a thesis is a challenging task for both native and non-native English speaking students. Despite a considerable number of studies on this specific genre elsewhere, there is a scarcity of work in Vietnam to help TESOL students to write a thesis. Furthermore, the Introduction is considered one of two most difficult chapters to write. This paper, therefore, presents a study on the rhetorical structure of Introduction chapters of twelve M.A. theses from the three universities in the South of Vietnam. Employing the modified CARS’ model by Bunton (2002), the results showed that three moves and 15 steps were employed by this group of non-native English writers despite the fact that they had little or no formal instruction on how to write this genre. Additionally, a new step was also identified in this corpus. These findings reflect Vietnamese students’ ability to conform to the norms and to adapt the norms to suit cultural expectations. This paper proposes practical implications for teaching this particular group of novice writers in Vietnam as well as in settings with similar cultural values on how to compose the Introduction section.